Per una ricostruzione giuridica dello stupro e della violenza sulle donne nell’età dello ius commune - Morello, Maria (Studi Urbinati, A - Scienze giuridiche, politiche ed economiche, 2013)
The present study intends to analyze that the crime of rape is understood, in the experience of common law, not only as an act of violence against the person who has sustained it, but above all as an attack on his honor, chastity, virginity and, as a logical consequence, to the marriage and the family. It is, without doubt, an offense which, in the political choice of his treatment, was affected, as well as continues to be affected, an intrinsic component sexist anchored in the cultural difficulty to get out of a pattern of unequal relationships, not just sex. Il presente studio intende analizzare il reato dello stupro inteso, nell’esperienza di diritto comune, non solo come atto violento nei confronti della persona che lo ha subito, ma innanzi tutto come un’aggressione al suo onore, alla castità, alla verginità, e come logica conseguenza, al matrimonio, alla famiglia. Si tratta senza alcun dubbio di un reato che, nella scelta politica del suo trattamento, ha risentito così come risente tuttora, di una intrinseca componente sessista incardinata nella difficoltà culturale di uscire da uno schema di rapporti, non solo sessuali, ineguali. DOI: 10.4459/STU.2013.005.IT